2019
DOI: 10.1167/iovs.19-27211
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PLCD3-OT1 Functions as a CeRNA to Prevent Age-Related Cataract by Sponging miR-224-5p and Regulating PLCD3 Expression

Abstract: PURPOSE. Long noncoding RNAs (lncRNAs) are important in disease progression and cellular functions. This study aimed to conduct global lncRNA profiling and characterize the role of lncRNA 1-phosphatidylinositol-4,5-bisphosphate phosphodiesterase delta 3-sence RNA 1 (PLCD3-OT1) in the progression of age-related cataract (ARC). METHODS. We performed lncRNA expression profiling of lens capsule from ARC groups and age-matched groups using high-throughput RNA-sequencing. Real-time PCR was conducted to detect the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 54 publications
(64 reference statements)
0
31
0
Order By: Relevance
“… 2 Several studies have shown that there are strong links of the cellular and molecular pathogenesis of ARC to DNA damage, DNA repair, oxidative stress, proteolysis, ubiquitination, apoptosis and autophagy. 3 7 In particular, the repairability of DNA oxidation damage plays a crucial role in maintaining the lens’ transparency. 7 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“… 2 Several studies have shown that there are strong links of the cellular and molecular pathogenesis of ARC to DNA damage, DNA repair, oxidative stress, proteolysis, ubiquitination, apoptosis and autophagy. 3 7 In particular, the repairability of DNA oxidation damage plays a crucial role in maintaining the lens’ transparency. 7 …”
mentioning
confidence: 99%
“… 3 7 In particular, the repairability of DNA oxidation damage plays a crucial role in maintaining the lens’ transparency. 7 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging studies reveal that the dysregulation of lncRNAs are impact the development and progression of cataract [31] [32] [33] [34] [35]. Compared with transparent lenses, KCNQ1OT1, TUG1, and H19 has identified to have signifi-cantly increased expression in age-related cataract [36] [37] [38]. The significant differential expression of lncRNAs in age-related cataract human lenses indicates that lncRNAs might play a crucial role in cataract formation ( Table 2).…”
Section: The Expression and Function Of Lncrnas In The Cataractmentioning
confidence: 99%
“…Therefore, H19 could be a useful marker in ARC. LncPLCD3-OT1 may act as a ceRNA to regulate the expression of PLCD3 by combining with mi-224-5p [38] and also plays a protective role in ARC [38]. Highly expressed TUG1 promotes lens epithelial cell apoptosis via sponging miR-421 [37].…”
Section: The Expression and Function Of Lncrnas In The Cataractmentioning
confidence: 99%